EFFECTS OF DIFFERENT APPROACHES IN RESOLVING CONFLICTS IN HRM - Šemso Ormanović,; Munir Talović,; Denis Čaušević,; Almir Mašala,; Ivor Doder,; Arnel Kaušić, (Sport Scientific And Practical Aspects, 2025)
Managing conflicts and conflict situations has more and more impact on contemporary management. Common conflicts can have long term consequences on work activities and financial results as well. Contemporary researches (behavioral point of view) state that resolving conflicts , apart from coordination of people, communication and motivation, is one of the most important elements of organizational management. The aim of this paper is reflected in systematic overview of different approaches in resolving conflicts, and their effects. Selection of the relevant papers for this study is conducted in Google scholar, MEDLINE , Kobson and EBSCO data base, including key words such as: conflict, way of solving and managing conflicts. 32 papers (of 156) fulfilled criteria for the final selection as part of this paper. 6 most common approaches in resolving conflicts are used in this paper and those are: avoidance, compromise, constructive way, giving in, resolving problems and imposition. Avoidance and compromise are two most common approaches. Although avoidance is considered to be a bad method in resolving conflicts, it is the most common. Also, compromise is one of the most common approaches in resolving conflicts. Compromise is considered to be a good method in resolving conflicts, but it's not favorable for all situations. Compromise is good method because it provides satisfaction for both parties involved in conflict and enables good collaboration and successful business activities of the company. Imposition is less common approach in resolving conflicts. This is because this approach has great number of contra effects and can be considered as harsh way of solving conflicts. Also this study showed that women use compromise and constructive way of resolving conflicts , while men use avoidance.